The aesthetic approach to the cohabitation of meaning between cinematic depth of field and theatrical presentation: Phenomenological study - Bahaa Abdul Mohsin Hasan; Maher Abdul Jabbar Ibrahim; Maher Majid Ibrahim (Basrah Arts Journal, 2023)
This research is concerned with studying the meanings inherent in theatrical performance in the light of the analytical mechanisms adopted by phenomenological philosophy, which examines how artistic works are performed, in an attempt to reach their first facts, by directing perception to the beginning of things، And then to associate with it a direct experience according to the thoughts manifested in the feeling. Thus, consciousness carries out the experience of meaning in theatrical performance, through a long series of cognitive practices, which can be intellectually and aesthetically compared to the (montage) practices that abound in the creative consciousness in the style of cinematic depth of field. The first chapter defines the problem of research (systematically) with the following question: What are the aesthetic approaches to the coexistence of meaning between the depth of the cinematic field and the structure of theatrical presentation. While the second chapter is determined (theoretically) by the following: the first research (the strategy of cohabitation of meaning in the depth of the cinematic field), the second research (the strategy of cohabitation of meaning in theatrical presentation) ، The third Topic (aesthetics of depth of field in theatrical performance). The third chapter is determined (procedurally) by the theatrical show (Shajar Murr), written and directed by (Abdul Majid Al-Hawas), for the year (2015). In addition to the fourth chapter, which includes the results and conclusions of the research. Finally, a list of sources, references and a summary of the research in English.